2020
DOI: 10.1093/mnras/staa518
|View full text |Cite
|
Sign up to set email alerts
|

The ASAS-SN catalogue of variable stars – VII. Contact binaries are different above and below the Kraft break

Abstract: We characterize ∼71, 200 W UMa type (EW) contact binaries, including ∼12, 600 new discoveries, using ASAS-SN V-band all-sky light curves along with archival data from Gaia, 2MASS, AllWISE, LAMOST, GALAH, RAVE, and APOGEE. There is a clean break in the EW period-luminosity relation at log(P/d) − 0.30, separating the longer period early-type (A sub-type) EW binaries from the shorter period, late-type (W sub-type) systems. The two populations are even more cleanly separated in the space of period and effective te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 79 publications
5
43
0
Order By: Relevance
“…In general, the classification of these systems in other catalogues is similar to ours. In particular, our periods exhibit good agreement with those derived by Jayasinghe et al (2020b). The mass ratio parameter of our total sample lies within the 0.30 < q < 3.74 range.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In general, the classification of these systems in other catalogues is similar to ours. In particular, our periods exhibit good agreement with those derived by Jayasinghe et al (2020b). The mass ratio parameter of our total sample lies within the 0.30 < q < 3.74 range.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 85%
“…We found an average value of ∼ 0.004, within the 0.00 < e < 0.04 range. For the contact EBs, we derived a median value of the eccentricity of e ∼ 0.0027, as expected for short-period systems (see, e.g., Chen et al 2018b;Jayasinghe et al 2020b). For the detached and semi-detached EBs, we obtained eccentricities of e ∼ 0.0047 and e ∼ 0.0058, respectively.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Each ASAS-SN camera has a 4.5 deg 2 field-of-view, 8″ pixels, and typical point-source FWHM of ∼2 pixels. With all-sky coverage, ASAS-SN data have already been used extensively for the analysis of Milky Way variable stars (Jayasinghe et al 2018(Jayasinghe et al , 2019a(Jayasinghe et al , 2019b(Jayasinghe et al , 2020a(Jayasinghe et al , 2020b(Jayasinghe et al , 2020cPawlak et al 2019;Percy 2019;Shields et al 2019;Auge et al 2020).…”
Section: Asas-sn Photometrymentioning
confidence: 99%
“…In case of the early-type CB, the J-band PL relation was derived in Chen et al (2016), while the optical PLC relation was presented in Pawlak (2016) based on 64 early-type CB located in the Large Magellanic Cloud. Using a much larger sample of CB, Jayasinghe et al (2020) showed that early-type and late-type CB follow a different PL relation. Finally, Sun et al (2020) divided CB into three sub-classes and derived the mid-infrared W 1-band PL relation for each of them.…”
Section: Introductionmentioning
confidence: 98%